THE INFLUENCE OF COMPENSATION, PERSON JOB FIT AND WORK ENVIRONMENT ON JOB SATISFACTION AT PT DIAN MEGA KURNIA - Ardiansyah, M. Ilham; Abadiyah, Rifda; Adji Kusuma, Kumara; Eka Febriansah, Rizky (JURNAL EKBIS, 2024)
Human resources are one of the company's most valuable assets. The balance of human resources should not be taken lightly, because this is the first step in human resource planning to create quality human resources. This research aims to determine the effect of person job fit compensation and work environment on job satisfaction at PT. Dian Mega Kurnia. The research method used in this research is a quantitative method. The population in this research is all employees at PT. Dian Mega Kurnia, totaling 120 employees. Based on the results of research conducted at PT. Dian Mega Kurnia, researchers know that there is a positive and significant influence of the compensation variable (X1) Person job fit (X2) and work environment (X3) on the job satisfaction variable (Y).